The trouble with babies - Mills, Claudia; Kath, Katie (New York : Alfred A. Knopf, 2016)
"Ten-year-old scientist Nora Alpers struggles with becoming an aunt and competing in her school science fair."--
Keywords: Science projects -- Fiction; Schools -- Fiction; Babies -- Fiction; Aunts -- Fiction; Infants -- Fiction; Science fairs -- Fiction; Schools -- Fiction